Practical Approaches for Determining the Structural Resolution Capability of X-ray Computed Tomography Measurement Tasks - Busch, Matthias; Hausotte, Tino (Metrology, 2024)
The structural resolution describes the ability of a measuring device to detect small structures on the surface of a component or test specimen by means of a quantitative value. However, the structure resolution in the computer tomograph depends on the object and must therefore be determined separately for each measurement task. Previous approaches to structure resolution determination are only related to test specimens. In this paper, less discrete approaches based on a circular pattern is presented, which can be integrated into the measured component. A voxel-based methodology as well as two surface-based methodologies are described. Investigation results regarding the effect of component position on the structural resolution are obtained on the basis of real CT measurements. A comparison is also made with the well-known hourglass method. The results show that the resolution depends on the object being measured, with similar values being obtained for the same object using different method
Keywords: Surface metrology; Structural resolution; Dimensional metrology; Siemens star; X-ray computed tomography